HUVECs-derived exosomes increase neovascularization and decrease limb necrosis in hindlimb ischemia - Ismail, Muhamad T.; Anggrahini, Dyah W.; Haryana, Sofia M.; Setianto, Budi Y. (Narra Sains Indonesia, 2024)
Chronic limb-threatening ischemia (CLTI) is the most severe manifestation of peripheral arterial disease (PAD) and imposes a significantly high burden due to its high risk of mortality and amputation. Revascularization is the first-line treatment for CLTI; however, the amputation rate remains high, and approximately one-third of patients are not eligible for this treatment. Therefore, there is an urgent need for more effective therapeutic strategies. The aim of this study was to investigate the effects and mechanisms of human umbilical vein endothelial cells (HUVECs)-derived exosomes on neovascularization and the degree of necrosis in a hindlimb ischemia model and to study the biological processes underlying their mechanisms. This is an in vivo experimental study with a post-test-only control group design. Forty BALB/c mice were randomized to receive injections of exosomes, conditioned media, and phosphate-buffered saline (PBS) one day after unilateral double ligation. A sham-operated group was also included as a control. Capillary density, arteriole lumen diameter, and histopathological necrosis were measured after seven days, while clinical necrosis was observed daily. MicroRNA profiling, in silico analysis, and transcriptomic analysis of vascular endothelial growth factor (VEGF) mRNA expression were performed to determine the possible biological processes. No amputation was found in the exosome group, as well as in the conditioned media and sham-operated groups, compared to three out of seven mice (43%) in the PBS group. The capillary density was higher in the exosome than in the PBS group (p=0.026). The arteriole lumen diameter in the exosome group was larger than in the PBS (p=0.033) and sham-operated (p=0.034) groups. The scores of clinical necrosis and histopathological necrosis in the exosome group were lower than the PBS group (p=0.005), while the histopathological necrosis scores were also lower but statistically insignificant. In silico analysis showed improvement in neovascularization and necrosis, possibly through energy regulation, PI3K/AKT and TGF-β activation, the ubiquitin-proteasome system, and tyrosine kinases receptors. HUVEC exosomes were associated with lower VEGF mRNA expression, which may indicate a more effective compensatory mechanism under ischemic conditions. The exosome group had the lowest VEGF mRNA expression compared to other groups, although the difference was not statistically significant. This study highlights that HUVECs-derived exosomes improve neovascularization and decrease necrosis in a hindlimb ischemia mice model, potentially by modulating several possible mechanisms.